Cognitive weaknesses or impairments on the NIH toolbox cognition battery in children and adolescents: base rates in a normative sample and proposed methods for classification - Cook, Nathan E.; Iverson, Grant L.; Karr, Justin E. (Frontiers in Psychology, 2025)
IntroductionThe National Institutes of Health Toolbox for Assessment of Neurological and Behavioral Function Cognition Battery (NIHTB-CB) is a brief neuropsychological battery for the assessment of crystalized (i.e., vocabulary and word reading) and fluid cognition (i.e., working memory, visual episodic memory, processing speed, and executive functions). This study examined the frequency of low NIHTB-CB scores and proposes flexible algorithms for identifying cognitive weaknesses and impairment among youth.MethodsParticipants were 1,269 youth from the NIHTB-CB normative sample who did not have a neurodevelopmental, psychiatric, or medical problem that might be associated with cognitive difficulties (53% boys and 47% girls; M = 11.8 years-old, SD = 3.0, range 7–17). The sample included the following racial and ethnic composition: 58.1% White, 17.8% Black or African American, 16.8% Hispanic, 1.7% Asian, 3.1% multiracial and ethnic identities, and 2.6% not provided. The frequency of obtaining low scores falling at or below several cutoffs were calculated and stratified by gender, age, and crystalized intellectual ability.ResultsConsidering the five fluid tests, nearly two-thirds of children and adolescents obtained one or more scores ≤ 25th percentile, half obtained one or more scores ≤ 16th percentile, between a third and a fourth obtained one or more scores ≤ 9th percentile, and nearly a fifth obtained one or more scores ≤ 5th percentile. We propose flexible, psychometrically derived criteria for identifying a cognitive weakness or impairment.DiscussionReferencing the base rates of low scores will help researchers and clinicians enhance the interpretation of NIHTB-CB performance among children with cognitive weakness or impairments that are neurodevelopmental or acquired.